A POSSIBLE RESEARCH METHOD OF IMPROVING PERFORMANCE CAPABLE KNOWLEDGE IN YOUTH BASKETBALL BY APPLYING COMPLEX SPORT CONDITIONING PROGRAM - Benedek Ágost NAGY (Cluj University Press, 2022)
From the aspect of the energy management, today's basketball player profile can be divided to four resources: physical, mental, spiritual and emotional (Woods, Jordan, 2010). We intended to observe the physical and mental part of this system. In every age category the athletes must increase their current potentials and reach the master or expert level (Baracskai,2007). Our research supervised the special basketball demands and the implementations to a training program that could help us to get a correct picture what, when, whom, how, where and why to teach (Winter, 1997). We researched the game performances as the ingredients of competitiveness based on a research of BSMPG (2010) that broke down the game and gave us exact scientific data of the modern basketball game. Purpose of study. Evaluate of every scientific hypothesis. Observing a special conditional program that is used yearly for a men university basketball team. The main goal of our research is to analyses the common effects of these programs for the game performances of the players. Understanding the sports carrier profiles of the participants regarding to their game performances. We'd like to find the details of the improvement of the game performances with a new methods that will separate the team and individual parts of the training process. Our hope is that our results, findings will be useful for planning the basketball practices. We look for the answers which practice topics, drills, tests, types and methods are the most effective to increase the special game performance in this model. Methods. We looked for the answers to why and how questions with our descriptive research methods. We guaranteed the validity of our work to choose our model systemically. We followed a longitudinal and panel investigation to guarantee the proper tests data. The data were analyzed statistically with ANOVA, regression, T probe. We have also used some expert explanation from the gathered data. Hudl video analyzer program. Results. The number of the high intensity sprint increases with the more ball possessions. (56/game, every 43-45 sec). The maximal vertical jumps of the players are predictable with the sum of the field goal attempts + blocks + rebounds (cc.10%). The defensive footwork is only 28 % of the playing time of a player. Conclusions. The longitudinal investigation was reasonable because the goals and the programs must be changed within the yearly practice plan. The teaching methods depends on the changes of the offensive strategy of the team. The more information we have about the physical and mental resources, the effective practice plan can be designed. A competitive conditional program can be properly designed that will consider the significant variants due to our findings. There is a significant connection between the performance of the practice program and the game performance.